Prison overcrowding - Prisoners’ fundamental rights and personality rights: Os direitos fundamentais e os direitos de personalidade dos reclusos - Guimarães, Ana Paula; Barata, Mário; Rebelo, Fernanda (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The inmate’s accommodation in prison must respect his/her dignity. Official data, up to December 2020, reveal overcrowding in some prisons. The article analyses the problem from a constitutional, personality rights, and penitentiary law perspectives, using legal and doctrinal sources. We conclude that overcrowding is a problem that must be overcome and that there is a clear gap between the law in the books and the law in action.